Employee judgments of and behaviors toward corporate social responsibility: A multi‐study investigation of direct, cascading, and moderating effects. (2nd July 2014) - Vlachos, Pavlos A.; Panagopoulos, Nikolaos G.; Rapp, Adam A.
Summary Do employee judgments of their organization's corporate social responsibility (CSR) programs relate to CSR‐specific performance and in‐role job performance? Can middle managers influence the formation of such judgments and what factors might moderate such cascading influences? To answer these yet unaddressed questions, we conduct three studies. Study 1 takes an organizational justice perspective and tests our baseline model. Results show that employees' CSR judgments trigger their affective commitment and performance on extra‐role CSR‐specific behaviors; however, extra‐role CSR‐specific performance is unrelated to in‐role job performance. Study 2 replicates Study 1's findings while, in addition, applies a social information processing approach and offers novel insights by demonstrating the cascading effects of managers' CSR judgments on employee CSR judgments. Investments made in CSR programs in order to improve employee judgments and behaviors may be unsuccessful if employees' CSR judgments are based on social information that remains unchanged. In addition to replicating the findings from studies 1 and 2, study 3 draws from middle management involvement and leadership theories to show that leadership styles and managers' involvement in implementing deliberate strategy can strengthen or weaken these cascading effects. This highlights the important role of middle managers as "linking pins" in the CSR strategy implementation process. Copyright © 2014 John Wiley & Sons, Ltd.